APLIKASI PERPINDAHAN KALOR PADA SETRIKA UAP - Fatiatun, Fatiatun; Fajeri, Mei Laelatul; Ni’mah, Azizatun; Faizin, Faizin (AL-QALAM: JURNAL KEPENDIDIKAN, 2022)
The use of electric irons can be used anywhere as long as there is an electrical installation. Electric irons lead to waste of electricity. In contrast to the use of a steam iron, it is a special choice when you need to iron a large number of clothes. A steam iron is an iron that can release steam from its base. The hot steam of the iron can help remove bad odors from clothes. When a steam iron is used for ironing clothes, heat transfer will occur. Heat transfer occurs because of the temperature difference in the material.